Electrochemical and thermodynamic study on the corrosion performance of API X120 steel in 3.5% NaCl solution - Khuram Shahzad (575887) (2020)
The present work studied the effect of temperature on the corrosion behavior of API X120 steel in a saline solution saturated with CO2 in absence and presence of polyethyleneimine (PEI) as an environmentally safe green inhibitor. The effect of PEI on the corrosion behavior of API X120 steel was investigated using destructive and non-destructive electrochemical techniques. The overall results revealed that PEI significantly decreases the corrosion rate of API X120 steel with inhibition efficiency of 94% at a concentration of 100 μmol L−1. The adsorption isotherm, activation energy and the thermodynamic parameters were deduced from the electrochemical results. It is revealed that the adsorption of PEI on API X120 steel surface follows Langmuir adsorption isotherm adopting a Physi-chemisorption mechanism. Finally, the samples were characterized using scanning electron microscopy (SEM) and atomic force microscopy (AFM) techniques to elucidate the effect of aggressiveness of corrosive media on the surface morphology and the corrosion performance of API X120 steel. The surface topography result indicates that the API X120 steel interface in PEI presence is smoother than CO2 with Cl− ions or Cl− ions only. This is attributed to the compact protective film limits the aggressive ions transfer towards the metallic surface and reduces the corrosion rate. Moreover, PEI inhibition mechanism is based on its CO2 capturing ability and the PEI adsorption on the steel surface beside the siderite layer which give the PEI molecules the ability to reduce the scale formation and increase the corrosion protection due to capturing the CO2 from the brine solution. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1038/s41598-020-61139-3